History of environmental impact assesment in Indonesia - F S Dhiksawan; S P Hadi; A Samekto; D P Sasongko (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2018)
This research on the history Environmental Impact Asessment (EIA) in Indonesia is aimed at obtaining an overview of the changes in regulations concerning EIA. It methods and materials in the form of library study including journals, books, and research documents on the history of EIA. The research produced an overview of the early history of EIA in Indonesia. The overview starts from the participation of the Government of the Republic of Indonesia in the Conference on the Human Environment (UNCHE) Stockholm in 1972. In 1973 Indonesia began inserting environmental consideration into the national development program based on the Decree of the People's Consultative Assembly Number IV of 1973 in the Broad Outlines of State Policy Chapter III Part B item (10). Environment law was firstly enacted in Indonesia in 1982. As time went by, the environmental laws went changes in 1997 and 2009. This law mandated the enactment of government regulation concerning EIA. EIA was first implemented in Indonesia based on the Government Regulation Number 29 of 1986. It was replaced with the Government Regulation Number 51 of 1993. Then It was revoked and replaced with Number 27 of 1999. After 3 (three) years replaced with Number 27 of 2012 on environmental license.